Grupo Opinião’s space: dissonant voices about its shutdow at Jornal do Brasil - Calixto Marques, Maria do Socorro (Sala Preta, 2015)
This paper aims at discussing the positions published at Jornal do Brasil (01/1980) about the shutdown of the theatrical space Opinião. The analysis of the corpus is framed on theoretical constructs about discourse and space, especially on the notions of utopia, heterotopia and discursive formation proposed by Michel Foucault and Michel de Certeau to address the spaces constructed through narratives. These two theoretical orientations consider the construction of space as a means to configure positions.